2000
DOI: 10.1103/physrevlett.84.5640
|View full text |Cite
|
Sign up to set email alerts
|

Multibubble Sonoluminescence Spectra of Water which Resemble Single-Bubble Sonoluminescence

Abstract: Multibubble sonoluminescence (MBSL) spectra of water from cavitation clouds were collected in the presence of different noble gases and at different acoustic intensities. Results show that at high acoustic intensity and with xenon as a dissolved gas the emission of the OH* radical becomes indiscernible from the continuum. These spectra resemble single-bubble sonoluminescence (SBSL) spectra. It is concluded that the source of emission in MBSL and SBSL can be the same, the difference in spectra is due to the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 21 publications
(35 reference statements)
1
35
1
2
Order By: Relevance
“…In particular, in Xe at 200 kHz, the 0-0 band is apparently not present. This feature could not be observed in previous studies, [4,6,8,12] in which the resolution was not sufficient.…”
contrasting
confidence: 69%
See 1 more Smart Citation
“…In particular, in Xe at 200 kHz, the 0-0 band is apparently not present. This feature could not be observed in previous studies, [4,6,8,12] in which the resolution was not sufficient.…”
contrasting
confidence: 69%
“…Didenko et al [8] compared multibubble sonoluminescence (MBSL) spectra of Ar-saturated water at 22 kHz and at 863 kHz. They observed a more prominent OH band at 310 nm at 22 kHz, whereas at 863 kHz the 340 nm shoulder was more pronounced and the intensity in the UV region was higher (peaking at 270 nm).…”
mentioning
confidence: 99%
“…The line emission of OH * radical in MBSL from water containing noble gases have been observed by Didenko et al [5] . When the driving pressure increased, the OH * radical peak became vague and could not be distinguished from the continuum.…”
Section: Dependence Of Line Spectra On the Driving Pressurementioning
confidence: 82%
“…Recently, more and more researches gradually closed the gap between them. In 2001, Didenko et al found that the spectral line of MBSL from water saturated with xenon almost vanished by increasing the driving pressure [5] . Young et al discovered the OH * radical line spectrum in extremely dim SBSL.…”
mentioning
confidence: 99%
“…Ref. [11] showed that, at high pressure, the spectra of MBSL are similar to those of SBSL in the solution dissolved with some noble gases; and it is probable that MBSL and SBSL have the same emission mechanism.…”
mentioning
confidence: 97%